Nutcracker syndrome: a review - Ramos-Peralta, Mariely; Lacayo-Valenzuela, Marlon E.; Sierra-Juárez, Miguel Ángel; Barrera-Mera, Baltazar (International Journal of Research in Medical Sciences, 2023)
Left renal vein (LRV) entrapment is an anatomic condition characterized by extrinsic compression of the renal vein and consequent impaired inferior vena cava (IVC) outflow. Nutcracker syndrome (NCS) can be caused by compression of the LRV between the aorta and the superior mesenteric artery or by compression of LRV between vertebral bodies and the aorta. The most common presentations in NS include pelvic or left flank pain, hematuria, gonadal varices, thus the hallmark manifestations of NCS may be related to renal venous congestion and increased pressure within the venous structures. Computed tomography, magnetic resonance imaging and doppler ultrasonography are reasonable imaging studies in patients with suspected NCS, but invasive evaluation with catheter venography and pressure measurement is often required to the definitive diagnosis. For now, it is not possible to standardize a treatment modality, although the trend towards endovascular management is clear; therapeutic strategies with open surgery should not be lost for those cases that correspond to this.